Selection of algo- mycobionts and creating of associative systems to improve plant productivity and recovery of degraded soils (Eurasian Journal of Ecology, 2016)
Mycorhiza can be used for reclamation of degraded soils and increase of efficiency and tolerance of plants to unfavorable factors of the environment. It was selected species of microalgae and mycorrhizal fungi toincrease the efficiency of mycorhiza, which inoculated to tomato plants in laboratory conditions. According to the content of pigments, protein in the leaves, activity of acid and alkaline phosphatase in tomato plantswas identified species of microalgae, which together with mycorrhizal fungi contribute to a significant increase in the studied parameters.
Keywords: mycorhiza; microalgae; tomatoes; pigments; phosphatase